Traumatic narrative of the pemberontakan PKI Madiun 1948 in the Ayat-Ayat yang Disembelih by Anaf Afifi and Thowaf Zuharon: A postmemory study - Santoso, Joko; Faruk, Faruk; Kussuji Indrastuti , Novi Siti (BAHASTRA, 2023)
This paper attempts to dismantle the pattern of trauma narratives developed in Indonesian literature by the second generation of the Pemberontakan PKI Madiun 1948. This second generation carries an Islamic narrative that is opposed to Communism. The narrative position of the Pemberontakan PKI Madiun 1948 is different from the G30S PKI 1965, in which the first PKI was the perpetrator, and the second PKI was the victim. The trauma narrative appears in the Ayat-Ayat yang Disembelih (2015) biography by Anaf Afifi and Thowaf Zuharon. The second generation lacks direct memory, which in Marianne Hirsch’s view, is postmemory. Accordingly, the theory used in this paper is Hirsch's postmemory, which believes that the second generation inherits trauma through investment in imagination, projection, and creation. The analytical method used is the methodological implications of postmemory theory with qualitative data. The pattern of the trauma narrative that emerges from the Islamic narrative to the PKI is; reflexive secondary first-person and mental transmission.